IMPACT OF SOCIO ECONOMIC FACTORS INFLUENCE ONLINE SHOPPING - Melbha, D. (International Journal of Research -GRANTHAALAYAH, 2018)
Since the internet has become a part and parcel of our existence, online shopping sites are burgeoning and getting popular with every passing day. Shopping, the definition and the concept, both have been revolutionized in the recent years. This is an inevitable part of progress, technically and socially. Presently social factors influence the online shopping. So I select this study, Impact of Socio Economic factors Influence online shopping. In this study I use 50 Private, public employees for data collection then this data collection purpose select Thiruvananthapuram city.